Prevalence and contributory factors to burnout in the New Zealand surgical specialist and registrar population - Dholakia, Jhanvi; Narayanan, Anantha; Smith, Nicholas (Frontiers in Public Health, 2025)
Burnout is a growing phenomenon among medical professionals due to aging patient populations and an increasing burden of chronic disease, in a resource constrained environment. We aim to quantify the prevalence of burnout in surgical specialists and registrars at a tertiary center in New Zealand and identify contributory factors, using a New Zealand based tool, the McEwan Burnout Questionnaire. Of the 110 people surveyed, 55% respondents had concern or high risk of burnout. Contributory factors were frustration with management, lack of resources and long working hours, with predominance toward fatigue and service provision over career progression among the registrar group. Bullying and harassment were reported more in the sub-specialty groups. More time in private practice appeared to be associated with less concern for burnout. These high rates of burnout require targeted interventions toward contributory factors to protect our workers and to maintain a sustainable workforce.